COMBINED EFFECTS OF VISCOUS DISSIPATION AND HEAT GENERATION ON NATURAL CONVECTION FLOW ALONG A VERTICAL WAVY SURFACE - Kabir, K. H.; Alim, M. A.; Andallah, L. S.; Mahjabin, Saika (Journal of Mechanical Engineering, 2015)
In this paper, the effects of viscous dissipation on natural convection flow along a uniformly heated vertical wavy surface with heat generation have been investigated. The governing boundary layer equations are first transformed into a non-dimensional form using suitable set of dimensionless variables. The resulting nonlinear systems of partial differential equations are mapped into the domain of a vertical flat plate and then solved numerically employing the Keller-box method. The numerical results of the surface shear stress in terms of skin friction coefficient and the rate of heat transfer in terms of local Nusselt number, the velocity as well as the temperature profiles are shown graphically and in tabular form for different values of physical parameters namely, viscous dissipation parameter Vd, heat generation parameter Q and Prandtl number Pr.